Parents' depression and loneliness during pregnancy and respiratory infections in the offspring: A prospective birth cohort study. - Linnea Schuez-Havupalo; Elina Lahti; Niina Junttila; Laura Toivonen; Minna Aromaa; Päivi Rautava; Ville Peltola; Hannele Räihä (Public Library of Science, 2022)
An association between maternal prenatal stress and increased rates of respiratory tract infections in the offspring has been described earlier. Data regarding the father's role is lacking. In this study our aim was to evaluate, whether mothers' and fathers' depressive symptoms and loneliness during pregnancy predict higher rates of respiratory tract infections in the offspring. In this longitudinal cohort study we gathered information on parental psychological risk during gestational week 20 using the BDI-II and UCLA loneliness scale questionnaires for the parents of 929 children. Loneliness was divided into social and emotional components, the former describing patterns of social isolation and the latter a perceived lack of intimate attachments. Episodes of acute otitis media, physician visits due to respiratory tract infections, and antibiotic consumption relating to respiratory tract infections were documented in the infants, excluding twins, from birth until 10 months of age using study diaries. Analyses were carried out by structural equation modeling, which provides dynamic estimates of covariances. Maternal depressive symptoms during pregnancy predicted higher rates of acute otitis media in the infant and maternal emotional loneliness predicted higher rates of physician visits. Acute otitis media, physician visits and antibiotic consumption in the infant were slightly less frequent for families who reported social loneliness in the father or mother. Associations remained when taking into account confounders. Maternal prenatal depression and emotional loneliness predicted a higher burden of respiratory tract infections in the offspring. The protective influence of parental social loneliness on the burden of respiratory tract infections in infants was not in line with our study hypothesis, but could be explained by reduced use of healthcare services in these socially isolated families. BACKGROUND METHODS RESULTS CONCLUSIONS